Governmentality of disability in the context of lifelong learning in European Union policy - Kauppila Aarno; Kinnari Heikki; Niemi Anna-Maija (Routledge Taylor & Francis Group, 2022)
The possibility to participate in education and lifelong learning has been introduced in EU disability policy in recent decades as one of the key means to improve the socioeconomic position of disabled persons. Simultaneously, lifelong learning has been developed as the defining concept of EU education policy to increase social cohesion and economic competitiveness. However, the education, employment rate and socioeconomic status of disabled persons have remained far below the EU average. In this article, we theorize governmentality to explore (1) how EU lifelong learning and disability policy discourses constitute and govern disabled persons and (2) how disabled persons are positioned in the policy discourses. The data consist of the most relevant EU policy documents concerning lifelong learning and disability policy in the twenty-first century. We argue that the policies constitute and govern disabled persons as a group who do not fulfil the premises set for the lifelong learner, and that consequently, policy discourses marginalize disabled persons instead.